Evaluating the Effects of 5-Hz Repetitive Transcranial Magnetic Stimulation With and Without Wrist-Ankle Acupuncture on Improving Spasticity and Motor Function in Children With Cerebral Palsy: A Randomized Controlled Trial - Li, Jiamin; Chen, Cen; Zhu, Shenyu; Niu, Xiulian; Yu, Xidan; Ren, Jie; Shen, Min (Frontiers in Neuroscience, 2021)
Objective: Explore the effect of wrist ankle acupuncture combined with 5Hz repetitive transcranial magnetic stimulation（rTMS）on improving spastic state and motor function of children with spastic cerebral palsy by measuring electrophysiological parameters and behaviors. Methods: Twenty-five children with spastic cerebral palsy were enrolled in a single-blind and randomized controlled trial. The control group received 20 sessions of 5 Hz rTMS over the affected hemisphere with 1000 pulses. The experimental group was given wrist ankle acupuncture on the basis of the control group. Gross motor function measure (GMFM-66), muscle tension and electrophysiological parameters of the two groups were assessed at baseline and post-intervention. Results: After treatment, the GMFM-66 scores in the same groups were significantly improved（p < 0.001）.Besides, the R-value of soleus, gastrocnemius and hamstring muscle decreased（p < 0.05）, and the results showed a trend of shortening MEP latency, increasing amplitude and duration（p < 0.05）.Compared to the controlled group, the experimental group displayed more excellent changes in the GMFM-66 scores and motor evoked potential latency. The statistical results showed that the increase of GMFM-66 score and the shortening of MEP latency in the experimental group was greater than that in the control group（p < 0.05）.But no significant differences were found in the assessment of muscle tension, amplitude and duration of motor evoked potentials between two groups（p ＞0.05）. Conclusion: Wrist-ankle acupuncture combined with 5 Hz rTMS is optimal to improve gross motor function and enhance the conductivity of corticospinal tract in children with cerebral palsy, but can’t highlight its clinical superiority in improving spasticity.